Newcastle Disease Case in Broiler Chicken - Angreini, Meliyantika; Balqis, Ummu; Etriwati, Etriwati; Hasan, Denny Irmawati; Aisyah, Siti; Salim, M. Nur; Nazaruddin, Nazaruddin; Darmawi, Darmawi (Jurnal Medika Veterinaria, 2023)
Newcastle Disease (ND) is a highly contagious disease with a high mortality rate, infecting poultry, and chickens are very susceptible to ND infection. The purpose of this case report is to find out how to diagnose ND disease in chickens. A 30-day-old white male broiler cadaver obtained from Pasar Lambaro, Aceh Besar was found dead in a holding cage with conjunctival hemorrhage and hair loss. Based on the physical examination of the external condition of the cadaver, it can be seen that the eye membranes are experiencing hemorrhage. There was nasal mucosa hemorrhage and mucous exudate in the nasal cavity. The oral mucosa was also found to have mucous exudate, while the cloaca was bleeding and there was residual green feces. The results of anatomic pathology examination found ptechie in the proventriculus and ventricles, swollen lungs with blackish red color and hemorrhage,with the presence of cheese. There was hemorrhage in other organs including trachea, intestines and tonsils, whilst the brain experienced hyperemia. The spleen was swollen and there were foci of necrosis. Based on the anamnesis, external examination, pathological anatomical examination, and histopathology, the diagnosis of the cause of death of broiler chickens was Newcastle Disease (ND).